Resistance of sheep from different genetic groups to gastrointestinal nematodes in the state of Sao Paulo, Brazil - Goncalves, T. C. [UNESP]; Alencar, M. M.; Giglioti, R. [UNESP]; Bilhassi, T. B. [UNESP]; Oliveira, H. N. [UNESP]; Rabelo, M. D.; Esteves, S. N.; Oliveira, M. C. S. (Elsevier B.V., 2018)
Infections by gastrointestinal nematodes cause large losses to sheep breeders. In the study reported here, the resistance to gastrointestinal nematodes was analyzed in sheep of adapted and non-adapted breeds, maintained in naturally infected pastures. A total of 134 females from seven genetic groups were monitored during 20 months: Santa Ines (OSI), Dorper (ODO), Texel (OTX), Ile de France (OIF), and animals from crosses of Santa Ines ewes with Dorper (ODS), Texel (OTS) and Ile de France (OIS) rams. Blood samples were collected monthly to determine the packed cell volume (PCV), and feces were collected at the same time to count the eggs per gram (fecal egg counts = FEC) and identify the genera of the prevalent parasites. The statistical analyses of the data showed significant differences (p < 0.05) regarding the genetic group, collection month and interaction of month with the genetic group on the FEC. The correlation estimates between FEC and PCV were negative and significant (p < 0.01). The OTS genetic group presented the lowest mean of FEC value. Concerning the nematode genera, the greatest prevalence was observed for Haemonchus spp. (85.6%), followed by Trichostrongylus spp. (10.8%), Oesophagostomum spp. (2.9%) and Cooperla spp. (0.7%). The results obtained in this study show that the crossing of the Texel and Santa Ines breeds can be considered an alternative for sheep production in the Southeast region of Brazil due to the lower egg output by gastrointestinal nematodes.
Keywords: Fecal egg counts; Sheep; Gastrointestinal parasites; Genetic groups; Susceptibility